A TAPERED-PERMITTIVITY ROD ANTENNA FOR GROUND PENETRATING RADAR APPLICATIONS - Chen C.C.; Rama Rao K.; Lee R. (My University, 2001)
A new dielectric rod antenna design modified from its previous version developed by Chen [IEEE Trans. Geosci. Remote Sens. (accepted for publication)] is presented. Such an antenna is useful in detecting small and shallow subsurface objects with excellent depth and spatial resolutions. These features make it useful in detecting small anti-personnel (AP) mines, pavement cracks and the surface layer. Broad bandwidth electromagnetic energy is fed into the rod from one end, guided along the rod and then radiated from the other end where the rod diameter is linearly tapered to a point. The tapered-permittivity design uses an additional permittivity taper to overcome the problem of a frequency-dependent pattern when high dielectric material is used for size reduction. This new design reduces the internal reflections at the tapered section and results in better efficiency and less antenna clutter.
Keywords: ANTENNA; GROUND PENETRATION RADAR; LANDMINES; MODELING